Structural changes in the thigh muscles following trans-femoral amputation - Putz, Cornelia; Block, Julia; Gantz, Simone; Heitzmann, Daniel; Dreher, Thomas; Lehner, Burkhard; Alimusaj, Merkur; Wolf, Sebastian Immanuel; Müller, Sebastian (European journal of orthopaedic surgery & traumatology, 2017)
IntroductionEarly ambulation is the principal objective in trans-femoral amputees. Postamputation modifications complicate the rehabilitation process due to a reduced control at the interface between stump and prosthesis. The aim of this study is to determine whether magnetic resonance imaging depicts the amount of fatty degeneration of the thigh muscles after trans-femoral amputation (TFA).MethodsA total of 12 patients following a TFA on the basis of a bone neoplasm or metastasis with an evaluable postoperative MRI were identified. Using the Goutallier classification, the fatty degeneration of the thigh muscles was analyzed in the middle (M) and at the distal end (E) of the residual limb at T1 (10.6 months) and T2 (25.6 months).ResultsAnalysis at two different levels showed different grades of fatty degeneration of thigh muscles after TFA at T1 and T2. Comparing fatty degeneration at both levels of the stump, the quadriceps femoris revealed a significant change (p = 0.01) at T1 and M. sartorius and adductor (p = 0.02) at T2.ConclusionsMRI is an excellent diagnostic tool to evaluate fatty degeneration after TFA. The highest amount of fatty degeneration of the quadriceps muscle was monitored within the first 10 months. Early physiotherapy is important to strengthen the remaining stump muscles during rehabilitation.
Published 21 February 2017
Gesehen am 23.10.2018